EFFECT OF LINGUAL TONSIL HYPERTROPHY ON STATE RESISTANCE OF ORAL MUCOSA - Nasibullin, B.A.; Andriyov, A.V.; Tagunova, I.K. (World of Medicine and Biology, 2014)
Research on 24 patients with lingual tonsil hypertrophy the state of resistance oral mucosa. Established of its weakening by reducing the amount of neutrophils in the contents of the oral cavity. The authors attribute this to sensibilisation of organism due to the influence of adverse factors (fungi, giardia).
Keywords: lingual tonsil; cellular composition of oral cavity; immune answer